2000
DOI: 10.1046/j.1365-2095.2000.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of microparticulate diets for early weaning of Atlantic cod Gadus morhua larvae

Abstract: Early weaning trials were conducted with cod larvae to investigate the effectiveness of microparticulate diets (microbound and microcoated) with and without lipid‐walled capsules (LWCs). The microparticulate diets were evaluated by measuring physical parameters of the diet in the water column (leaching and settling rate), palatability (intestinal fullness), performance of the diet (survival and growth), and examination of the diet in the larval intestine (histological analysis). A feeding trial was conducted u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
2
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 28 publications
2
51
2
5
Order By: Relevance
“…In many fish species, early weaning of fish larvae may reduce the quality of fish, and skeletal malformations have been frequently reported in this process [3,5]. The cause of skeletal malformations in early weaning larvae may be due to the malnutrition supply to fish larvae and early cannibalisms (mechanical damage) during the weaning process [2,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many fish species, early weaning of fish larvae may reduce the quality of fish, and skeletal malformations have been frequently reported in this process [3,5]. The cause of skeletal malformations in early weaning larvae may be due to the malnutrition supply to fish larvae and early cannibalisms (mechanical damage) during the weaning process [2,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In practice, weaning of most temperate marine fish species such as Trachinotus ovatus and Seriola lalandi are usually commenced after metamorphosis [1,2]. Previous studies have demonstrated that early introduction of micro-particles diets to marine fish larvae can have positive effects on fish adapting to the micro-particles diets [3,4]. But premature introduction of the micro-particles diets can also inhibit fish growth and survival as fish cannot digest the artificial diets when their digestive system is not properly developed [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid leaching in water has been evaluated in several studies (Lopez-Alvarado et al 1994;Baskerville-Bridges & Kling, 2000;Yufera et al 2002;Onal & Langdon, 2004), these researchers observed that leaching can be extensive and there are major differences between types of food and between different components.…”
Section: Introductionmentioning
confidence: 99%
“…The development of microdiets for larval marine fish, such as the Pacific bluefin tuna (Thunnus orientalis) (Haga et al, 2010(Haga et al, , 2011Takeuchi & Haga, 2015), red sea bream (Pagrus major) (López-Alvarado & Kanazawa, 1994a;Teshima, Koshio, Ishikawa, Alam & Hernadez, 2004), olive flounder (Bai, Cha & Wang, 2001;Takeuchi et al, 2003;Wang et al, 2004;Ji et al, 2013), gilthead seabream (Sparus aurata) (Saleh et al, 2013), European sea bass (Dicentrachus labrax) (Person-Le Ruyet, Alexandre, Thebaud & Mugnier, 1993) and Atlantic cod (Gadus morhua) (Baskerville-Bridges & Kling, 2000;Johnson, Cook, Nicklason & Rust, 2009) have been successfully made. Especially, Takeuchi et al (2003) reported that a mixture of microparticle diets containing two different molecular weight peptides (1000-2000 and 30,000 Da) was a good source of protein and this type of diet can be given to olive flounder from the larval to juvenile stage.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of the complete replacement live food with microdiet alone for some marine fish larvae seems to be limited (Baskerville-Bridges & Kling, 2000;Takeuchi et al, 2003;Wang et al, 2004;Faulk & Holt, 2009;Tang, Chen & Wu, 2010;Alam et al, 2013;Li et al, 2013), but the combination of microdiet with live food effectively improved the survival and growth of the larval stages of marine fish (Kolkovski, Koven & Tandler, 1997;Yúfera et al, 2000;Teshima et al, 2004;Ji et al, 2013). Teshima et al (2004), in particular, showed that live food (Rotifer and Artemia) could be completely replaced with a zein-microbound diets containing a molecular weight of 1000 and 3000 Da soybean peptides or with the combined half amount of zein-microbound diet containing a molecular weight of 1000 Da soybean peptides and live food for 30 days after hatching (DAH) in red sea bream larvae; however, for 15 DAH olive flounder larvae, the combined half amount of zein-microbound diet containing a molecular weight of 1000 Da soybean peptide and live food only.…”
Section: Introductionmentioning
confidence: 99%